Differentiation of the third instar of forensically important fly species in Thailand - Sukontason K. (2014)
Differentiation of the third instar of forensically important fly species in Thailand was performed using light microscopy, based on their morphological criteria for fly identification. Four species of the family Calliphoridae [Chrysomya rufifacies (Macquart), Chrysomya megacephala (F.), Chrysomya nigripes Aubertin, and Lucilia cuprina (Wiedemann)] and two species of the family Muscidae [Musca domestica L. and Hydrotaea (=Ophyra) spinigera Stein] were examined in this study, with the features of the anterior spiracles, dorsal spines between the prothorax and mesothorax, and posterior spiracles being emphasized. The comparisons, presented herein, should be helpful for forensic practitioners to readily distinguish the third instars of fly species found associated with human cadavers, before their use for further forensic investigations. © 2004 Entomological Society of America.